2022
DOI: 10.21873/cgp.20345
|View full text |Cite
|
Sign up to set email alerts
|

RAB27A and RAB27B Expression May Predict Lymph Node Metastasis and Survival in Patients With Gastric Cancer

Abstract: Background/Aim: RAB27A and RAB27B are involved in exosome secretion. To date, there have been many attempts to elucidate the roles of RAB27A and RAB27B in the prognosis of various cancer types. The association of RAB27A and RAB27B expression with the clinical and pathological features was evaluated in patients with stomach cancer. Materials and Methods: A total of 360 patients who had undergone surgery for stomach cancer between January 1999 and December 2007 at Gyeongsang National University were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…High expression of Rab27b has been correlated with poor survival in patients with solid cancers, such as colorectal, pancreatic, and esophageal squamous cell cancer (21,(42)(43)(44)). An et al also reported that Rab27b expression predicts lymph node metastases and survival in GC patients (45). These findings suggest that Rab27b expression in tumor tissues can serve as a useful biomarker of poor prognosis in various malignancies.…”
Section: Rab27b Knockdown Suppressed Peritoneal Metastasis Of Gastric...mentioning
confidence: 84%
“…High expression of Rab27b has been correlated with poor survival in patients with solid cancers, such as colorectal, pancreatic, and esophageal squamous cell cancer (21,(42)(43)(44)). An et al also reported that Rab27b expression predicts lymph node metastases and survival in GC patients (45). These findings suggest that Rab27b expression in tumor tissues can serve as a useful biomarker of poor prognosis in various malignancies.…”
Section: Rab27b Knockdown Suppressed Peritoneal Metastasis Of Gastric...mentioning
confidence: 84%
“…The oncogene Rab27b, a member of the Rab family, facilitates the growth and invasion of some kinds of tumors. 79 Rab27b mediated the radioresistance of GBM cells, as demonstrated by Nishioka et al. 80 Following radiation, Rab27b causes the release of epithelial regulatory protein (EREG), which interacts with EGFR to encourage the development of neighboring cells.…”
Section: Autocrine Pathwaysmentioning
confidence: 97%
“…Exosome formation requires RAB GTPases, tetraspanins (CD63, CD81, CD82, and CD9), and lipid-modifying enzymes such as sphingomyelinases [ 44 ]. RAB27A promotes the metastatic potential of melanoma cells by promoting the formation of pro-invasive exosomes [ 44 ] and regulates the secretion of exosomes in patients with gastric cancer [ 45 ]. The downregulation of RAB27A decreases the secretion of exosomes in gastric cancer cells and inhibits the peritoneal metastasis of gastric cancer cells without affecting the invasion potential of cancer cells [ 46 ].…”
Section: Biogenesis Of Exosomesmentioning
confidence: 99%